Disease Burden of Meningitis Caused by Streptococcus pneumoniae Among Under-Fives in China: A Systematic Review and Meta-analysis - Biying Wang; Wanjing Lin; Chen Qian; Youyi Zhang; Genming Zhao; Weibing Wang; Tao Zhang (Infectious Diseases and Therapy, 2023)
Abstract Introduction Streptococcus pneumoniae is the leading cause of meningitis, with a case fatality of up to about 50%. Children younger than 5 years are at greater risk for pneumococcal meningitis compared with other populations. It is of significant importance to provide a comprehensive understanding of the burden of pneumococcal meningitis among under-fives in the low pneumococcal conjugate vaccine (PCV) coverage period in China. Methods A systematic review was conducted. We searched both English (PubMed, Ovid-EMBASE, Biosis, Web of Science, and Cochrane) and Chinese (CNKI, Wanfang, and ViP) databases for studies on bacterial meningitis in China published between January 1980 and July 2022. Ineligible studies were excluded based on study design and data integrity. Heterogeneity was assessed with I 2 and estimates of bacterial meningitis morbidity and mortality were pooled using random-effects models. Subgroup analysis was conducted to trace the source of the heterogeneity and summarize average estimates. Results A total of 13,082 studies were identified in the literature, and 56 studies were finally included for data analysis. The estimated incidence of pneumococcal meningitis was 2.10 cases per 100,000 children younger than 5 years each year (95% CI: 0.59–7.46), with a pooled case fatality rate of 24.59% (95%CI: 19.35–30.28%) in China. It was estimated that 1617.16 (95% CI: 454.35–5744.78) pneumococcal meningitis cases and 548.86 (95% CI: 474.80–627.62) deaths occurred among under-fives in China in 2020. Streptococcus pneumoniae played an important role in the etiology of confirmed bacterial meningitis cases, with a pooled proportion of 22.05% (95% CI: 17.83–26.27%). The most prevalent serotypes were 6B, 14, 19F, 19A, and 23F, which were preventable with a vaccine. Conclusions Pneumococcal meningitis remains one of the most important health problems among children younger than 5 years in China. Immunization programs should be promoted to avoid preventable cases and deaths.